دورCRP السائل الدماغي الشوكي في تشخيص التهاب السحايا الإنتاني عند البالغين - لايقة, عيسى; زريق, يوسف; أبوعلي, هديل (Latakia University Journal -Medical Sciences Series, 2019)
BACKGROUND: The rapid diagnosis of meningitis to start appropriate treatment, according to pathogens, is a major challenge in our country, so we need a quick, reliable, and cost-effective diagnostic test. OBJECTIVE: To determine the role of CRP in CSF in distinguishing between different types of meningitis Materials and Methods: This was a cross-sectional study at Tishreen Hospital in Lattakia, Syria, included 52 patients with symptoms and clinical signs of meningitis. Lumbar puncture was performed with complete analyzes on the CSF sample with CRP level measured in CSF by turbidimeter method. Results were statistically significant when p-value <5%. RESULTS: The mean CRP in cerebrospinal fluid was 19.84 ± 4.8 mg / l, while in partially treated bacterial meningitis patients was 19.80 ± 4.7 mg / l, in patients with viral meningitis 0.71 ± 0.1 mg / l, In patients with viral meningoencephalitis 0.90 ± 0.3 mg / l. At a cut-off point 11,2 mg / l, CRP sensitivity was 88,23% in the diagnosis of pyogenic meningitis and specificity was100%, and at a cut-off point 10,9 mg / l, CRP sensitivity was 90,9% in the diagnosis of partially treated bacterial meningitis and specificity was100% CONCLUSION: The mean CRP in CSF was higher in bacterial meningitis (PM, PTBM) than viral meningitis and meningoencephalitis with high sensitivity and specificity that makes it a reliable, easy, fast and cost-effective test for diagnosis of bacterial meningitis. خلفية: إن التشخيص السريع لالتهاب السحايا وتحديد نمطه لوضع العلاج المناسب هو تحدٍ كبير في بلدنا، لذا نحتاج لاختبار تشخيصي سهل وسريع، موثوق وقليل التكلفة. الهدف: تحديد دور ال CRP في السائل الدماغي الشوكي CSF في التمييز بين الأنماط المختلفة لالتهاب السحايا المواد والطرق: كانت هذه دراسة تحليلية مستعرضة أجريت في مستشفى تشرين الجامعي في اللاذقية، سوريا على 52 مريضً لديهم أعراض وعلامات سريرية موجهة لالتهاب السحايا، تم إجراء بزل قطني مع تحاليل كاملة على عينة ال CSF مع قياس مستوى ال CRP في ال CSF بطريقة التحليل العكارية. تمَ اعتبار النتائج هامة احصائياً عندما p-value < 5%. النتائج : بلغ متوسط ال CRP في ال CSF عند مرضى التهاب السحايا الجرثومي القيحي 19.84 ± 4.8 ملغ/ل، في حين بلغ عند مرضى التهاب السحايا الجرثومي المجهض 19.80 ± 4.7 ملغ/ل، عند مرضى التهاب السحايا الفيروسي 0.71 ± 0.1 ملغ/ل، وعند مرضى التهاب السحايا والدماغ الفيروسي 0.90 ± 0.3 ملغ/ل، عند نقطة قطع 11.2 ملغ/ل بلغت حساسيةCRP السائل الدماغي الشوكي 88.23% في تشخيص التهاب السحايا الجرثومي القيحي، فيما بلغت النوعية 100%. وعند نقطة قطع 10.9 ملغ/ل بلغت حساسية CRP السائل الدماغي الشوكي 90.9% في تشخيص التهاب السحايا الجرثومي المجهض PTBM، فيما بلغت النوعية 100%. الخلاصة: كان متوسط الـ CRP في السائل الدماغي الشوكي التهاب السحايا الجرثومي (القيحي والمجهض) أعلى من متوسط الـ CRP في السائل الدماغي الشوكي في التهاب السحايا الفيروسي والتهاب السحايا والدماغ الفيروسي مع حساسية ونوعية عاليتين مما يجعله اختبار موثوق سهل وسريع وقليل التكلفة لتشخيص التهاب السحايا الجرثومي القيحي والمجهض.